The effect of yttria-stabilized zirconia (YSZ) addition on the synthesis of βeta-tricalcium phosphate (β-TCP) from biogenic hydroxyapatite - Zainurin, Mira Azah Najihah; Zainol, Ismail; Jaafar, Che Nor Aiza; Mudhafar, Mustafa (Universiti Putra Malaysia, 2023)
The utilization of β-tricalcium phosphate (β-TCP) in medical field has been on demand for their excellent biocompatibility, bioactivityand solubilityproperties. This material can be produced through degradation of hydroxyapatite (HA) at high temperature. In this research, biogenic hydroxyapatite from fish scales (FsHA) was selected as pre-cursor for the synthesis of β-TCP. The effect of yttria-stabilized zirconia (YSZ) addition on degradation of FsHA into β-TCP have been investigated. Different amount of YSZ ranging from 5 to 15 wt% were mixed with FsHA and ball milled into fine powder. The mixture was then sintered at temperature of 1200°C. The materials were characterized using X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) and scanning electron microscope (SEM). The results from FTIR, XRD and SEM-EDX analyses proved that the presenceof β-TCP in the sintered sampleat 1200 oC. The percentage of β-TCP was calculated ranging from 17 to 21 % as analyzed from XRD pattern. It was found that the FsHA/YSZ composite with 5 wt% of YSZ addition produced the highest composition of β-TCP with smallest crystallite size at the ideal sintering temperature of 1200°C. The results also shown that the FsHA was not fully converted into β-TCP during sintering. Furthermore, XRD analysis also clearly shown the presence of another phase known as calcium zirconate (CaZrO3)phase.The triphasic calcium phosphate (BCP) has high potential to be used as biomaterials for bone fillers applications.